The Use of Drill, Vocabulous (Vocabulary Various) and Computer Assisted Language Learning (CALL) in Learning Vocabulary - Fauzia, Nur; Lolita, Yuri (English Education Department, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya, 2018)
This study investigates the effectiveness of three vocabulary learning methods that are Contextual Clues, Dictionary Strategy, and Computer Assisted Language Learning (CALL) in learning vocabulary among ESL learners. First, it purposes at finding which of the vocabulary learning methods namely Vocabulous (Vocabulary Various), Drill and CALL that may result in the highest number of words learnt in the immediate and delayed recall tests. Second, it compares the results of the PreÃ¢â‚¬Âtest and the Delayed Recall PostÃ¢â‚¬Âtest to determine the differences of learning vocabulary using the methods. A quasiÃ¢â‚¬Âexperiment tested the effectiveness of learning vocabulary using Dictionary Strategy, Contextual clues, and CALL involved 40students. Qualitative procedures included the collection of data from interviews which were conducted to triangulate the data obtain from the quantitative inquiries. Findings from the study using ANOVA revealed that there were significant differences when students were exposed to Vocabulous, Drill and CALL in the immediate recall tests but not in the Delayed Recall PostÃ¢â‚¬Âtest. Also, there were significant differences when t test was used to compare the scores between the PreÃ¢â‚¬Âtest and the Delayed Recall PostÃ¢â‚¬Âtest in using the three methods of vocabulary learning. Although many researchers have advocated the relative effectiveness of Vocabulous, Drill, and CALL in learning vocabulary, the study however, is still paramount since there is no study has ever empirically investigated the relative efficacy of these three methods in a single study.